Polymorphism and estimation of the number of MhcCyca class I and class II genes in laboratory strains of the common carp (Cyprinus carpio L.) - Stet, R J; van Erp, S H; Hermsen, T; Sültmann, H A; Egberts, E (Developmental and comparative immunology, 1993)
Restriction fragment length polymorphisms (RFLPs) have been identified in the Mhc of the carp (MhcCyca) using class I (Cyca-Z) and class II (Cyca-YB) specific probes. The K1-5 and K2-1 probes were obtained as PCR products after amplification of genomic DNA from a European carp using primers deduced from genomic sequences, and were shown to be 90% and 80% similar to Cyca-Z exon 3 and Cyca-YB exon 2 sequences, respectively. Six carp strains of different geographical origins and genomic status were studied. In homozygous gynogenetic carp strains the class I probe K1-5 hybridized to 9-12 fragments, whereas the class II probe K2-1 hybridized to 3-5 fragments. Thus, the Cyca consists of multiple class I and class II genes. The level of polymorphism of the Cyca genes of the strains studied was calculated as the percentage of polymorphic fragments among the total number of fragments observed, and was shown to be 70% for class I and 40-66% for class II genes. In addition, a possible correlation was investigated between a serologically defined locus K, which was demonstrated previously to incorporate class I-like characteristics, and molecular genotyping using the class I probe. Two gynogenetic families, which were serologically typed K1 and K2 homozygous, also differed in their RFLPs using a class I probe. This would suggest that the K locus is part of the Cyca complex.